Research on the Impact of Digital Transformation on Corporate Innovation Performance - Zhi, Jing (Transactions on Economics, Business and Management Research, 2024)
Vigorously developing the digital economy and promoting digital transformation is a strategic choice to seize new opportunities arising from the new wave of technological revolution and industrial transformation. Companies must actively advance the innovative development of the digital economy, strengthen, optimize, and expand their digital capabilities to enhance their technological innovation capacity. This paper takes Chinese A-share listed companies from 2010 to 2022 as the research sample, conducting an empirical analysis of the impact of digital transformation on corporate innovation performance. It further explores the mediating effect of increased investment in human capital, summarizing the influence path of “Digital Transformation—Human Capital Investment—Innovation Performance”. The results show that digital transformation significantly enhances corporate innovation performance, empowering companies to improve their innovation outcomes. The impact of digital transformation on innovation performance varies by geographical location, ownership structure, and industry, with a more substantial effect on companies in the eastern region, non-state-owned enterprises, and high-tech firms. Based on these findings, the paper proposes feasible policy recommendations from both governmental and corporate perspectives.